2016
DOI: 10.1002/art.39655
|View full text |Cite|
|
Sign up to set email alerts
|

Toll‐like Receptor 9 Signaling Is Augmented in Systemic Sclerosis and Elicits Transforming Growth Factor β–Dependent Fibroblast Activation

Abstract: Objective Although transforming growth factor β (TGFβ) is recognized as being a key trigger of fibroblast activation in systemic sclerosis (SSc), prominent innate immunity suggests that additional pathways contribute to disease persistence. Toll‐like receptor 9 (TLR9) is implicated in autoimmunity and fibrosis; however, the expression, mechanism of action, and pathogenic role of TLR9 signaling in SSc remain uncharacterized. The aim of this study was to explore the expression, activity, and potential pathogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 61 publications
3
26
0
1
Order By: Relevance
“…TGF‐β is an important profibrotic molecule that mediates fibroblast activation, proliferation, and myofibroblastic differentiation . Previous studies have demonstrated that induction of TLR9 protein expression in lung and skin fibroblasts from idiopathic pulmonary fibrosis (IPF) and systemic sclerosis patients can be mediated by profibrotic cytokines when stimulated with TGF‐β . In the present study, TGF‐β stimulation induced a significant increase in TLR9 mRNA compared to untreated NPDFs, and low levels of TGF‐β mRNA were observed by CpG A stimulation.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…TGF‐β is an important profibrotic molecule that mediates fibroblast activation, proliferation, and myofibroblastic differentiation . Previous studies have demonstrated that induction of TLR9 protein expression in lung and skin fibroblasts from idiopathic pulmonary fibrosis (IPF) and systemic sclerosis patients can be mediated by profibrotic cytokines when stimulated with TGF‐β . In the present study, TGF‐β stimulation induced a significant increase in TLR9 mRNA compared to untreated NPDFs, and low levels of TGF‐β mRNA were observed by CpG A stimulation.…”
Section: Discussionsupporting
confidence: 49%
“…showed that IL‐6 and IFN‐α were increased in lung fibroblasts stimulated with CpG DNA, but in contrast, TNF‐α expression did not become elevated. Fang et al . stimulated skin fibroblasts in patients with systemic sclerosis with CpG DNA, which led to detectable TLR9‐mediated responses.…”
Section: Discussionmentioning
confidence: 99%
“…Hierarchical clustering stratified the biopsies into the previously described diffuse-proliferative and inflammatory gene expression subsets (31,32). Inflammatory intrinsic subset biopsies ( Figure 9C, lower panel), accounting for ~34% of all SSc biopsies in the present study, showed significant enrichment with the TLR4-responsive gene signature (Pearson correlation = 0.2) compared with other biopsy subsets (2 samples, 2-tailed t test, P < 0.001) (33). Analysis of a replication microarray dataset comprising 28 skin biopsies from an independent cohort of 15 dcSSc patients (GSE32413) (32) confirmed significantly higher TLR4-responsive gene signatures in biopsies mapping to the inflammatory intrinsic subset (comprising 50% of all SSc biopsies; average Pearson correlation = 0.1, t test P < 0.05) (Supplemental Figure 9).…”
Section: Md2/tlr4 Blockade Abrogates Damp-induced Ex Vivo Fibrotic Rementioning
confidence: 60%
“…Nuclei were identified using DAPI. Subcellular distribution of immunofluorescence was evaluated under an immunofluorescence microscope or Zeiss UV Meta 510 confocal microscope or a Nikon C2 or A1Si confocal microscope and quantitated using ImageJ (12,33).…”
Section: Methodsmentioning
confidence: 99%
“…Mmp9, Ccr5, Mgst1), the SUMO modification (e.g. Sumo1, Ildr2), NOS/hypoxia signaling (e.g.Itga2, Fn1, Ndufa6, Cox6a2), and Toll-like receptor (TLR) pathways (e.g.Tlr9, Oas3) [3,28,[32][33][34][35]. Some of the genes including Notch3, Mmp9, Ildr2, Sumo1, Rpl39, and Ndufa6 also altered in human lung biopsy samples of pulmonary fibrosis with the similar tendency to that in our mouse models, data from GEO database (Suppl.…”
Section: Gene Expression Profiles Validated the Anti-fibrosis Effect mentioning
confidence: 99%